PROTOTYPE MONITORING SUHU PADA KANDANG AYAM BROILER MENGGUNAKAN SENSOR SUHU DHT11 BERBASIS MIKROKONTROLER ESP8266 DI DESA DAMPANG KABUPATEN BULUKUMBA - Alam Syah; Husni Sulaiman; Nurwahid Syam (Journal System Information And Computer, 2023)
Abstract – This study aims to: To design a tool that can monitor temperature in broiler chicken coops using the DHT11 temperature sensor based on the Esp8266 Microcontroller, Dampang Village, Bulukumba Regency. To find out how the temperature monitoring prototype in broiler chicken coops uses a DHT11 temperature sensor based on the ESP8266 microcontroller in Dampang Village, Bulukumba Regency. This study used the prototype research method (prototyping) aimed at developing the model into the final system. Based on the results of this study it can be concluded that: Prototype monitoring temperature in broiler chicken coops using the DHT11 temperature sensor based on the ESP8266 microcontroller in the village of Dampang, Bulukumba district which was designed or built using the ESP8266 microcontroller, DHT11 sensor, relay, jumper cables, lights incandescent, Fan, and the Blynk application. The Blynk application can run on smartphone specifications with a minimum of 1.5 GB of RAM with a minimum Android version 4.0 and above. Implementation of a temperature monitoring prototype in a broiler coop using a DHT11 temperature sensor based on an ESP8266 microcontroller in the village of Dampang, Bulukumba district, which can adjust the temperature automatically in the chicken coop, if the temperature shows 35o C then the fan will rotate automatically, if the temperature has is at 33o C the fan will stop rotating, and if the temperature shows 28o C then the incandescent lamp will turn on automatically, if the temperature has reached 31o C then the incandescent lamp will stop burning.